2015
DOI: 10.1104/pp.15.00622
|View full text |Cite
|
Sign up to set email alerts
|

Half-of-the-Sites Reactivity of the Castor Δ9-18:0-Acyl Carrier Protein Desaturase

Abstract: Fatty acid desaturases regulate the unsaturation status of cellular lipids. They comprise two distinct evolutionary lineages, a soluble class found in the plastids of higher plants and an integral membrane class found in plants, yeast (Saccharomyces cerevisiae), animals, and bacteria. Both classes exhibit a dimeric quaternary structure. Here, we test the functional significance of dimeric organization of the soluble castor D9-18:0-acyl carrier protein desaturase, specifically, the hypothesis that the enzyme us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…While ethylene is known to regulate fruit ripening positively through inducing ripening-associated genes and autocatalytic ethylene production 38 , two seemingly conflicting features of SlMYB75 -OE tomatoes are their high level of ethylene production and delayed ripening (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…While ethylene is known to regulate fruit ripening positively through inducing ripening-associated genes and autocatalytic ethylene production 38 , two seemingly conflicting features of SlMYB75 -OE tomatoes are their high level of ethylene production and delayed ripening (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary modeling suggests that, once a functional SAD5-A allele is formed, pollinator-mediated selection would rapidly increase its allele frequency [33]. Third, SAD proteins act as dimers and recent biochemical work has shown that only one desaturase subunit is active at a time and that heterodimers with one LOF and one functional subunit have the same net activity as homodimers with two functional subunits, whereas only LOF/LOF homodimers (25%) are inactive [40]. Thus, ancestor proteins of SAD5, or their combinations in heterozygotes, may well have possessed desaturase activity sufficient for alkene production and associated pollinator attraction.…”
Section: The Evolutionary Trajectory Of Modern Sad5 May Have Containementioning
confidence: 97%
“…Half-of-sites reactivity is a general phenomenon in enzymology reported in numerous homodimeric proteins (37)(38)(39)(40)(41)(42)(43)(44). The homodimeric crystal structures of ACMSD invariably show one active site being well-ordered and another somewhat disordered, making ACMSD a candidate for half-of-sites reactivity (8,24,27,28).…”
Section: A New Insight For Half-of-sites Reactivity In Homodimeric Enzymesmentioning
confidence: 99%